The Fibrosis and Immunological Features of Hypochlorous Acid Induced Mouse Model of Systemic Sclerosis - Meng, Meng; Tan, Jieqiong; Chen, Weilin; Du, Qian; Xie, Bin; Wang, Nian; Zhu, Honglin; Wang, Kangkai (Frontiers in Immunology, 2019)
Fibrotic animal model is critical for the pathogenesis investigations and drug explorations in Systemic sclerosis (SSc).The bleomycin (BLM)-induced mouse model is the classical and most widely used fibrosis model. However, traditional subcutaneous injection of BLM does not cause diffuse skin lesions and rarely induces lung fibrosis or autoantibody production. Hypochlorous acid(HClO)-induced mice are a more representative model that have diffuse cutaneous lesions, lung fibrosis and renal involvement, along with the production of serum anti-DNA topoisomerase 1 autoantibodies. While the fibrosis and immunological features of this model are not fully elucidated. Here, we used different concentrations of HClO (1:55, 1:70, and 1:110 NaClO: KH2PO4, hereafter named HClO55, HClO70, and HClO110, respectively) and injected BALB/c mice subcutaneously for 6 weeks, and also used HClO110 for different time courses (4, 5 and 6 weeks). HE and Masson’s trichrome staining were used to observe the morphological changes. Immunohistochemistry or real-time PCR was used to detect inflammatory infiltrates, important fibrosis pathways and pro-inflammatory mediator expression. Flow cytometry was used to detect the alteration of immune cells in mouse spleen. Skin and lung fibrosis were most obvious in the HClO55 group. In the HClO110 group, dominant inflammatory infiltrates was found at 5 weeks, and significant fibrosis was found at 6 weeks. Then we explored the fibrosis and immunological profiles in the HClO110 (6 weeks) group. Important fibrosis pathway proteins such as TGF-β, NF-κB, Smad3, p-Smad3, STAT3, and p-STAT3 were significantly elevated. Increased infiltration of CD4+T cells, CD8+T cells, CD20+B cells, and myofibroblasts was found both in skin and lung tissues. However, decreased CD4+T cells, CD8+T cells, monocytes and macrophages and increased CD19+B cells was found in the spleen tissues. The mRNA expression of fibrosis mediators such as IL-1β, IL-6, IL-17, IL-33, TNF-α, and CTGF was also upregulated. In conclusion, HClO induced fibrosis mouse model displayed systemic immune cell infiltrates, pro-inflammatory mediator release, vasculopathy and fibrosis, which better mimicked human SSc than BLM-induced mice.